Wacana Tradisi Jawa dalam Tayangan Acara Tingkeban Anak ke-Dua Lesti Kejora - Amalia Juang L; Arike Amanda S; febriana santika (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines how Javanese culture is represented in the tingkeban ceremony of the second child of celebrity couple Lesti Kejora and Rizky Billar, using a critical discourse analysis approach influenced by the post-structuralist theory of Michel Foucault. The tingkeban tradition, originally a private ritual, has been reconstructed into digital entertainment, focusing on aesthetics, religious narratives, and the ideal image of motherhood. By applying Foucault’s concepts of discourse, power, and subject formation, this article reveals how cultural meanings, gender roles, and celebrity identities are formulated through discursive mechanisms on social media platforms. The findings indicate that the event is not merely a means of cultural preservation, but also a symbolic exercise of power that reinforces social norms and preferred identities, particularly those aligned with the middle-class values. In this context, tradition becomes a contested site for the construction and negotiation of meaning in contemporary discourse.